INTERNATIONAL LABOR RIGHTS A CATEGORICAL IMPERATIVE? - Ahmed, Kamil (Revue de droit de l'Université de Sherbrooke)

(untitled) (Revue de Droit de l’Université de Sherbrooke, 2004)
Labor standards are a contentious issue in International Trade Law and particularly reflect the dichotomy between developed and underdeveloped states. The first tend to protect labor rights extensively and the latter rarely do so. Since its inception, the International Labor Organization has significantly bettered the protection of labor rights, but this is not the best forum to uniquely pursue given its lack of enforcement mechanisms. The World Trade Organization until now has also failed to protect international labor rights and a comprehensive agreement to this effect is improbable, at least in the short to mid-term. A new form of soft-regulation has however developed: the Corporate Code of Conduct. Presently, we are at the genesis of an era where multi-national corporations are beginning to possess obligations at International Law. The advantage of Corporate Codes of Conduct is that they are flexible, transnational and as international and adaptable as a corporation can be. This paper argues that the combined application of International Labor Organization conventions, World Trade Organization rules and Corporate Codes of Conduct can significantly improve the protection of labor rights, despite a general lack of rule enforcement mechanisms.